Progress towards implementing a research agenda towards post-mining transitions - Measham, T.; Walker, J.; Haslam McKenzie, F.; Samper, A.; Brereton, D.; Boggs, G. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mine closure does not have a great track record. While there are some important exceptions, too few mines have achieved effective closure, lease relinquishment and a positive legacy. Many of the reasons for this have been articulated through the Mine Closure Conference community. At the same time, there is a growing momentum towards thinking beyond closure and focusing on how to achieve better post-mining transitions by repurposing sites and delivering improved social and economic outcomes, and recognising the crucial role of First Nations people. Following the foundational stage of the Cooperative Research Centre for Transformations in Mining Economies, a research agenda was put forward focusing on four key aspects. The first of these is the need for deliberation on what post-mining transition means in different contexts. The second is the need to develop ways to incorporate a wider range of values into closure post-mine transition planning, to ensure future sustainability in livelihoods and environment. The third is the importance of integration and forecasting across a spectrum of biophysical, social and economic aspects of mine closure and transition. The fourth is to focus on elevating the scale for mine closure and transition planning, from the site to the regional scale and beyond. This paper summarises progress to date by the Cooperative Research Centre for Transformations in Mining Economies and adjacent work towards implementing this agenda.